SCIENTOMETRIC PORTRAIT OF NOBEL LAUREATE AHMED HASSAN ZEWAIL - Kademani, B.S.; Kalyane, V.L.; Kumar, Vijai (Malaysian Journal of Library and Information Science, 2001)
Scientometric analysis of 246 papers by Ahmed Hassan Zewail, the Nobel laureate in chemistry (1999), published between 1976 and 1994 in diverse fields: femtochemistry (62), reaction rates and IVR (56), general reviews (49), coherence and optical dephasing phenomena (27), solids: magnetic resonance and optical studies (13), liquids and biological systems(9), local modes in large molecules (9), molecular structure from rotational coherence (8), solar energy concentrators(7), and other studies(6). Data was analyzed for authorship pattern with his 103 collaborators. Highest collaborations were with P. M. Felker (39), M.Dantus (19), and L.R.Khundkar (16). The highest number of collaborators (38) were during 1986 – 90, followed by 30 during 1981 – 1985. His productivity coefficient was 0.52 which is a clear indication of consistent publication productivity behaviour throughout his 19 years of research.